The Savvy Survey #10: In-Person-Administered Surveys - Glenn D. Israel; Jessica L. Gouldthorpe (EDIS)
In-person-administered surveys are a type of face-to-face interview that collects mainly quantitative data from a number of individuals and can be useful for collecting information from low-literacy audiences or obtaining very detailed information from agricultural producers or business owners about needs or program outcomes. As part of the Savvy Survey Series, this 7-page fact sheet presents the construction, development, and implementation of in-person surveys, as well as how to prepare an introductory script, train interviewers, and manage the survey process. Written by Glenn D. Israel and Jessica L. Gouldthorpe, and published by the Agricultural Education and Communication Department, December 2015.